Discretization of Geometric Models - Keyan, Arthur J. (Mathematical Problems of Computer Science, 2021)
We are interested in 2D cutting and packing problem with irregularly shaped objects. In previous work the author has presented the description of the two - dimensional modeling program of irregularly shaped objects. The next step of achieving the optimal arrangement of any irregular shape details on the surface is the discretization of geometric models. In this paper a solution to this problem is given. The solution is described in steps.